Intramedullary Spinal Rosai Dorfman disease- A rare cause of quadriparesis - Sandeep Velicheti; R. Rajakulasingam; K. Kalyan; G. Rajesh; R. Botchu (Journal of Orthopaedic Reports, 2022)
Background: Rosai Dorfman Disease (RDD) is histiocytosis associated with lymphadenopathy. Spinal involvement is uncommon and seen in 1%. Most of the spinal lesions are extradural and intradural extramedullary. Intramedullary RDD is extremely rare. Case report: We report a rare case of quadriparesis in 24 year old male due to intramedullary RDD of cervicothoracic region and review the literature. Conclusion: The rare cases of intramedullary RDD should be included in the differential diagnosis of young patient presenting with quadriparesis or paraparesis.